MONKEYPOX DISEASE TREATMENT BY TECOVIRIMAT ADSORBED ONTO SINGLE-WALLED CARBON NANOTUBE THROUGH DRUG DELIVERY METHOD - Fatemeh Mollaamin; Sara Shahriari; Majid Monajjemi (Journal of the Chilean Chemical Society, 2023)
In this work, it has been investigated the Monkeypox disease which occurs in both humans and animals by infection with a double-stranded DNA virus having the symptoms consisting of fever, fatigue, headache, and muscle pains like flu. Tecovirimat drug can be applied in prohibition of monkeypox virus through adsorbing onto surface of single-walled carbon nanotube (SWCNT) as the drug delivery method due to direct electron transfer principle which has been studied by density functional theory (DFT) methods.Therefore, it has been accomplished the B3LYP/6-311+G (2d,p) level of theory to estimate the susceptibility of SWCNT for adsorbing tecovirimat through nuclear magnetic resonance and thermodynamic parameters. In other words, the data explained that the feasibility of using SWCNT and tecovirimat becomes the norm in drug delivery system which has been achieved by quantum calculations due to physico-chemical properties of NMR and IR methodologies.